2019
DOI: 10.1007/s00221-019-05685-x
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of visual aesthetic appreciation: insights from non-invasive brain stimulation

Abstract: During the last decade, non-invasive brain stimulation techniques have been increasingly employed in the field of neuroaesthetics research to shed light on the possible causal role of different brain regions contributing to aesthetic appreciation. Here, I review studies that have employed transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) to investigate neurocognitive mechanisms mediating visual aesthetic appreciation for different stimuli categories (faces, bodies, pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 115 publications
(215 reference statements)
1
16
0
1
Order By: Relevance
“…Since the aesthetic experience or perception of beauty is often associated with artwork 2 , the underlying brain mechanisms in the aesthetic process for artwork have been discussed extensively 3 6 . More recently, the field of neuroaesthetics has grown and expanded to involve non‑invasive brain stimulation 7 to investigate the brain–behavior causal relationship and the computational aesthetic approach 8 , 9 to bridge the gap between experimental and theoretical studies. Although studies conducted to date have generally suggested that various regions along the visual dorsal and ventral pathways are involved in the aesthetic experience, no unified view has been reached 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the aesthetic experience or perception of beauty is often associated with artwork 2 , the underlying brain mechanisms in the aesthetic process for artwork have been discussed extensively 3 6 . More recently, the field of neuroaesthetics has grown and expanded to involve non‑invasive brain stimulation 7 to investigate the brain–behavior causal relationship and the computational aesthetic approach 8 , 9 to bridge the gap between experimental and theoretical studies. Although studies conducted to date have generally suggested that various regions along the visual dorsal and ventral pathways are involved in the aesthetic experience, no unified view has been reached 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For millennia, questions concerning art and aesthetic experiences have been debated (Danto, 1964;Bell, 1914;Collingwood, 1958;Else, 1938) and continue to drive real-life behaviour via attendance to museums, galleries and live performances. Neuroaesthetics research has identified the involvement of widespread brain networks spanning visual, motor affective and cognitive information processing units during aesthetic judgments (Boccia et al, 2016;Brown et al, 2011;Cattaneo, 2019Cattaneo, , 2020Chatterjee, 2003;García-Prieto et al, 2016;Kirsch et al, 2016;Pearce et al, 2016). However, current understanding of how the brain constructs aesthetic experiences is in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…This points to what has been referred to as "Cirque du Soleil effect", where we may enjoy witnessing the spectacular movements of talented performers that are more "unlike us" and, thus, do not belong and cannot be incorporated into our sensorimotor repertoire (Cross, Kirsch, Ticini, & Schütz-Bosbach, 2011;Kirsch, Urgesi, & Cross, 2015). Converging evidence for such an "unlike me" aspect of aesthetic experience has come from studies using brain stimulation methods to modulate activation of motor areas during aesthetic experience (reviewed in Cattaneo, 2020;Kirsch, Urgesi, & Cross, 2015). Indeed, these studies have shown that lowering motor activation with inhibitory stimulation of fronto-parietal motor areas may be associated to greater aesthetic appreciation of natural stimuli, such as dance movies (Calvo-Merino, Urgesi, Orgs, Aglioti, & Haggard, 2010) and static or dynamic body postures (Cazzato, Mele, & Urgesi, 2016), artifacts (Ticini, Urgesi, & Kotz, 2017)() or artworks (Nakamura & Kawabata, 2015).…”
Section: Discussionmentioning
confidence: 98%